Possibility of immediate treatment to soybean processing by-products using screw extrusion: a mini review - Shen, Yue; Huang, Xiaolong; Nan, Yujia; Yu, Hansong; Lyu, Bo (Frontiers in Sustainable Food Systems, 2024)
Soybeans are an important oil and protein supply crop, but the utilization of by-products from its processing products has never been effectively resolved, while a large number of nutritional resources have been wasted and environmental pollution is serious, restricting the sustainable development of the industry. The critical problem of soybean processing by-products includes excessive levels of microorganisms, residual proteins, metal ions, and other substances. Because the screw extrusion process has potentially advantageous processing characteristics, it appears that it’s just the right solution to the above problem of soybean processing by-products. We propose that this technology may be a potentially scalable technology for the immediate processing of soybean by-products. This paper reviews the theoretical foundations in existing research, briefly discusses the technological advantages, feasibility, and potential risks of this process, and hopes that researchers may pay attention to this technique and conduct feasibility studies.